The Drosophila EGF receptor homolog (DER) gene is allelic to faint little ball, a locus essential for embryonic development. - Schejter, E.D.; Shilo, B.Z. (Cell, 1989)
Recessive lethal mutations in the genetic locus of the Drosophila EGF receptor homolog (DER) were isolated. Identification of mutations in the gene is based on assays of DER protein autophosphorylation activity. Most DER alleles show little or no in vivo autophosphorylation. The ability to monitor these activities in vivo and in vitro offers a preliminary insight into the functional defects in the different mutant proteins. The identification of the DER locus was also confirmed by partial rescue of the mutant phenotype with a DER P-element construct. Homozygous DER mutants display a complex embryonic phenotype. Most notably, the anterior structures deteriorate, ventral denticle bands are missing, the germ band does not retract, and the central nervous system shows a collapse of commissure and midline pattern. Mutations in DER were shown to be allelic to the previously described locus faint little ball.